2011
DOI: 10.4049/jimmunol.1002993
|View full text |Cite
|
Sign up to set email alerts
|

TLR Regulation of SPSB1 Controls Inducible Nitric Oxide Synthase Induction

Abstract: The mammalian innate immune system has evolved to recognize foreign molecules derived from pathogens via the TLRs. TLR3 and TLR4 can signal via the TIR domain-containing adapter inducing IFN-β (TRIF), which results in the transcription of a small array of genes, including IFN-β. Inducible NO synthase (iNOS), which catalyzes the production of NO, is induced by a range of stimuli, including cytokines and microbes. NO is a potent source of reactive nitrogen species that play an important role in killing intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 61 publications
4
34
0
Order By: Relevance
“…These observations suggest that arctigenin could manifest its effect on iNOS activation through multiple mechanisms. However, recent studies have shown that CHIP is not the only E3 ubiquitin ligase capable of mediating downregulation of iNOS [31,32]. Thus, involvement of other E3 ligases in arctigenin-induced degradation of iNOS needs to be further studied.…”
Section: Discussionmentioning
confidence: 98%
“…These observations suggest that arctigenin could manifest its effect on iNOS activation through multiple mechanisms. However, recent studies have shown that CHIP is not the only E3 ubiquitin ligase capable of mediating downregulation of iNOS [31,32]. Thus, involvement of other E3 ligases in arctigenin-induced degradation of iNOS needs to be further studied.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence is indeed accumulating showing that the formation of ROS represents an essential pathway of TLR-dependent signaling in cells from immune and non-immune origin, which occurs mainly through the activation of various NOX isoforms (Tsung et al, 2007;Ogier-Denis et al, 2008;Gill et al, 2010). In addition, the pro-inflammatory signaling cascades triggered by TLR engagement enhance the expression of iNOS, and thus promotes the generation of NO (Lewis et al, 2011;Shweash et al, 2011). In turn, the concomitant generation of O 2 .-(by NOXs) and NO .…”
Section: Role Of Tlr Activation In the Generation Of Oxidantsmentioning
confidence: 99%
“…SPSB1, 2 and 4 are similar both in amino acid sequence and in function. We, and others, have recently shown that inducible nitric oxide synthase (iNOS/NOS2) is a physiological target of the mammalian SPSB1 and SPSB2 proteins, suggesting a role for these proteins in regulating the innate immune response (70)(71)(72). SPSB1, 2 and 4 interact via their SPRY domain with a DINNN motif in the N-terminal region of iNOS and through the SOCS box-associated CRL ubiquitinate iNOS causing it to be degraded by the proteasome.…”
Section: Spry Domain Socs Box Proteinsmentioning
confidence: 99%